1991
DOI: 10.1007/bf01887382
|View full text |Cite
|
Sign up to set email alerts
|

Computed tomographic findings of ruptured hepatic malignancy

Abstract: Massive hemorrhage from ruptured hepatocellular carcinoma is uncommon. We report our experience in three cases of ruptured hepatocellular carcinoma diagnosed by computed tomography (CT). CT was useful in detecting ruptured hepatocellular carcinoma showing the parenchymal tumor per se, defining the extent of the hematoma, and showing serial density changes with the age of the hematomas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

1996
1996
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…Shock is present in 33–90% of patients . The rate of clinical diagnosis of ruptured HCC has gradually improved owing to the development of imaging modalities such as ultrasonography (US) and computed tomography (CT); in previous studies, 75% of the diagnoses were confirmed by CT, US or both . However, some cases are still initially diagnosed on emergency exploratory laparotomy .…”
Section: Introductionmentioning
confidence: 99%
“…Shock is present in 33–90% of patients . The rate of clinical diagnosis of ruptured HCC has gradually improved owing to the development of imaging modalities such as ultrasonography (US) and computed tomography (CT); in previous studies, 75% of the diagnoses were confirmed by CT, US or both . However, some cases are still initially diagnosed on emergency exploratory laparotomy .…”
Section: Introductionmentioning
confidence: 99%
“…Doppler ultrasound and CT imaging are useful in delineating hemoperitoneum and liver tumors and CT is specifically useful in detecting HCC rupture by visualizing the tumor and blood loss. The peripheral location and protrusion of the tumor and discontinuity of the hepatic surface and surrounding hematoma with high attenuation on CT are very helpful signs in the diagnosis of ruptured HCC [16]. In this case study, contrast extravasation of the tumor and pooling of blood at the periphery of the liver due to hemoperitoneum were helpful in establishing the diagnosis.…”
Section: Discussionmentioning
confidence: 79%
“…Ac- we could not confirm whether the sentinel vessels were occluded hepatic veins or injured feeding arteries. We presumed that the sentinel vessels were injured feeding arteries, based on previous evidence of vascular injury in ruptured HCCs (17,(21)(22)(23)(24).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have suggested that HCC rupture is caused by the disruption of friable feeding arteries, leading to hemorrhage and increased intra-tumoral pressure from the local bleed (8,9,(14)(15)(16)(17)(18). During hepatic angiography, we have previously observed that ruptured HCCs are associated with disproportionately in whom TAE were not performed.…”
Section: Introductionmentioning
confidence: 99%